2010
DOI: 10.1097/jom.0b013e3181d53dc2
|View full text |Cite
|
Sign up to set email alerts
|

Italian National Register of Occupational Cancers: Data System and Findings

Abstract: Despite some limits and incompleteness pertaining to data flow, the results of this study are in accordance with epidemiological findings on occupational cancer risks. The collection of information on occupational cancers is of primary importance to plan targeted prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…[1][2][3] Nevertheless, epidemiological studies found that different types of silica dust have various potentials to cause adverse health effects. Prolonged inhalation of silica dust is associated with the development of pulmonary diseases, such as silicosis, chronic obstructive pulmonary disease, and lung cancer.…”
mentioning
confidence: 99%
“…[1][2][3] Nevertheless, epidemiological studies found that different types of silica dust have various potentials to cause adverse health effects. Prolonged inhalation of silica dust is associated with the development of pulmonary diseases, such as silicosis, chronic obstructive pulmonary disease, and lung cancer.…”
mentioning
confidence: 99%